The Portrayal of Indonesian Image in 2007 Kompas Selected Short Stories: Social Problems, Criticisms and Hopes - Akun, Akun (Lingua Cultura, 2010)
Article aimed at exploring social problems reflected in 15 selected short stories printed in Kompas during 2007 both explicitly and implicitly. Specifically, this research is focused on the mapping of dominant social problems raised by the short stories, the social criticisms strongly voiced by the authors and the hopes of a better situation implicitly reflected in these interesting short stories. This study applies the Defamiliarization Effect promoted by Bertolt Brecht and Negative Dialectics or Negative Knowledge by Theodor Adorno, specifically in analyzing the literary works as a criticism tool. The result of the research shows that phenomena of social problems current lately in Indonesian context like identity, poverty, corruption, religious tensions, moral degradation, politics dirtiness, minority group problems, social security, natural disasters and the like are clearly seen and teased in these writings.